2002
DOI: 10.1002/jcp.10190
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic deformation of migratory efferent lymph‐derived cells “trapped” in the inflammatory microcirculation

Abstract: The cellular immune response depends on the delivery of lymphocytes from the lymph node to the peripheral site of antigenic challenge. During their passage through the inflammatory microcirculaton, the migratory cells can become transiently immobilized or "trapped" in small caliber vessels. In this report, we used intravital microscopy and temporal area mapping to define the dynamic deformation of efferent lymph-derived mononuclear cells trapped in the systemic inflammatory microcirculation. Mononuclear cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
1
0
2
Order By: Relevance
“…The intravital videomicroscopy studies of the control microcirculation showed that Ͼ99% of the observed cells had flow velocities Ͼ2 m͞msec; no reproducible regions of lymphocyte slowing were observed (16). In contrast, the oxazolonestimulated microcirculation demonstrated reproducible lymphocyte slowing in focal regions of the microcirculation ( Fig.…”
Section: Resultsmentioning
confidence: 93%
“…The intravital videomicroscopy studies of the control microcirculation showed that Ͼ99% of the observed cells had flow velocities Ͼ2 m͞msec; no reproducible regions of lymphocyte slowing were observed (16). In contrast, the oxazolonestimulated microcirculation demonstrated reproducible lymphocyte slowing in focal regions of the microcirculation ( Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Так, при СВ интенсивность системной альтерации должна быть сопоставима с локальным повреждением в очаге классического воспаления, чтобы реализовался феномен системной воспалительной микроциркуляции (системного микрососудистого васкулита). Таким образом, феномен воспалительной микроциркуляции является атрибутом очага классического воспаления [50], а на системном уровне -шокогенным проявлением СВ [3]. Проблема заключается в том, что однозначно идентифицировать СВ с помощью измерения уровня СВР можно только в ограниченном числе случаев, например при тысячекратных повышениях в крови некоторых цитокинов («цитокиновый шторм» -признак гиперергической фазы СВ).…”
Section: особенности концепции документа «сепсис-3» в россииunclassified
“…6 a und b). Zur besseren Kontrastierung können Farbstoffe i. v. appliziert werden, zur Verfolgung zum Beispiel von Lymphozyten, die in definierten Gefäßabschnitten markiert und resuspendiert werden [19]. Die wichtigste Einschränkung der Intravitalmikroskopie ist jedoch die limitierte Eindringtiefe.…”
Section: Intravitalmikroskopieunclassified